Pharmacological effects of ginseng and ginsenosides on intestinal inflammation and the immune system - Zhao, Linxian; Zhang, Tongbo; Zhang, Kai (Frontiers in Immunology, 2024)
Intestinal inflammatory imbalance and immune dysfunction may lead to a spectrum of intestinal diseases, such as inflammatory bowel disease (IBD) and gastrointestinal tumors. As the king of herbs, ginseng has exerted a wide range of pharmacological effects in various diseases. Especially, it has been shown that ginseng and ginsenosides have strong immunomodulatory and anti-inflammatory abilities in intestinal system. In this review, we summarized how ginseng and various extracts influence intestinal inflammation and immune function, including regulating the immune balance, modulating the expression of inflammatory mediators and cytokines, promoting intestinal mucosal wound healing, preventing colitis-associated colorectal cancer, recovering gut microbiota and metabolism imbalance, alleviating antibiotic-induced diarrhea, as we as relieving the symptoms of irritable bowel syndrome. In addition, the specific experimental methods and key control mechanisms are also brieﬂy described.